Collusions of fact and fiction : performing slavery in the works of Suzan-Lori Parks and Kara Walker - Saal, Ilka (Studies in theatre history and culture., 2021)
"Collusions of Fact and Fiction is the first book-length study in the field to discuss the works of Suzan-Lori Parks and Kara Walker in conjunction with each other and to establish them as exemplary for a larger generational shift in how late twentieth century African American artists have been addressing the histories and legacies of New World slavery"--